What is the investment loss due to uncertainty? - Theodore Panagiotidis; Panagiotis Printzis (Leibniz-Institut für Ost- und Südosteuropaforschung (IOS), 2019)
We investigate the effect of uncertainty on investment. We employ a unique dataset of 25000 Greek firms' balance sheets for 14 years covering the period before and after the eurozone crisis. A dynamic factor model is employed to proxy uncertainty. The investment performance of 14 sectors is examined within a dynamic investment model. Robust GMM estimates of the investment rate model reveal a high degree of heterogeneity among these sectors. Overall uncertainty affects negatively investment performance and this effect substantially increased in the years of crisis. Agriculture and Mining are the least affected and the most affected ones include Manufacturing, Real Estate and Hotels. Focusing on the response of investment to uncertainty, it emerges that (relative) smaller firms are affected more compared to larger ones.
urn:nbn:de:101:1-2020032409150119565617
Keywords: C23; D22; D81; D92; G31; 330; Greek firms; Uncertainty; Volatility; GMM; Panel data